The Evaluation of Polymer-Modified BNA-Blend - Matar, Mohammed I. D.; Suparma, Latif Budi; Siswosukarto, Suprapto; Rochmadi (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Asphalt roads are the lifeblood of people who live in the desert regions in Libya, where the environment there considered the hottest and arid region in the world. So, this harsh environment damages the asphalt road and make it unsafe. High temperature and wheel loads are essential factors that damage the asphalt road. Rutting is one criterion for the failure of this asphalt mixture, which disturbs passengers and increases the maintenance costs of asphalt pavement. This research evaluated the physical and rheological characteristics of BNA-Blend modified with elastomeric polymers. Five types of polymers used, namely, NR (Latex), EVA, SBS, and EPDM at five percentages (2, 4, 6, 8, & 10%) of each kind of polymers. The fluorescent microscopy images show homogenized for NR, EVA, and SBS mixtures, except the EPDM mixture. The physical properties of these polymer-modified BNA-Blend have measured through experimental tests as penetration, softening point, and ductility test, and viscosity test to measure rheological properties. Besides, the influence of the homogeneity of polymer-modified BNA-Blend has investigated. The fluorescent microscopy images show homogenized for NR, EVA, and SBS mixtures, except the EPDM mixture. The rheology test result of polymer changed BNA-Blend increases the softening point, viscosity and decreases the penetration.